State of Statelessness for Displaced Persons Through the Doctrine Of Ubuntu: South African Domestic Perspective and International Law Obligation Through the Lens Of Khoza V Minister of Home Affairs [2023] 2 ALL SA 489 (GP) (The Pretoria Student Law Review, 2025)
The notion of statelessness and the positioning of the South African government in protecting its territorial integrity have been attributed to preserving its financial capability to cater for its nationals while imposing administrative and financial constraints on those who come to its shores seeking asylum due to instability in their respective regions, often leaving them displaced and undocumented. Subsequently, the criteria for defining statelessness remain contested, making the state privy to act unreasonably unjust in certain circumstances. Consequently, the government implicitly foreshadows its privy policy by scrutinising such applications as a programme that aims to ensure that it does not have an excess of foreigners who may negatively affect service delivery and cause unwanted issues like crime. As a result, stateless people are perceived as interfering with the allocation of the national fiscus. The notion of statelessness will, however, be explored as this paper progresses through the case of Khoza v Minister of Home Affairs and Others by showing how a decolonised and transformative endeavour of ubuntu should be practised. As such, the idea of ubuntu will be affirmed through the international obligation of international human rights while simultaneously arguing that Africans have not become so assimilated as to regard other Africans as strangers, to such an extent that the systems in place today are based on national self-centred interests that hold Western influence. This influence, as the paper unfolds, will prove that stateless persons in South Africa tend to be subversively (implicitly) discriminated against when they apply for nationality. Therefore, a xenophobic stance from an institution such as the Department of Home Affairs gains enormous adherence when it processes applications, especially for Africans.
Keywords: statelessness; stateless persons; ubuntu; foreigners; national interests; identity crisis